Italian interiors - Puglisi, Luigi Prestinenza , 1956- (Birkhauser, Basel, Switzerland : Actar Birkhauser, 2012)
Italian interior design has been distinguished for decades by its innovative power and courage, not only on an aesthetic level but also in its use of new materials and combinations thereof. This book presents a selection of designs from 2000 to 2009, realized in Italy and other countries, including the US, France, the UK, Israel, and Dubai
1. Introduction -- 2. Hotels and restaurants -- 3. Retail -- 3. Offices and cultural buildings -- 4. Private residences -- 5. Appendix
"This book is a modified English edition of the Italian origianl version "
Keywords: Interior architecture -- Italy -- History -- 21st century -- Pictorial works; Interior decoration -- Italy -- History -- Pictorial works